IDDF2019-ABS-0193 Expression of autophagy proteins in the duodenum of patients with functional dyspepsia. (June 2019) - Du, Lijun; Chen, Binrui; Cen, Mengsha
Abstract : Background: Functional dyspepsia (FD) is considered as an idiopathic disorder with undefined mechanisms. Autophagy plays a role in regulating inflammation, which has been proposed to be associated with the development of FD. In present study, we sought to gain a knowledge on the level of autophagy proteins (beclin1, p62/SQSTM1) in FD patients. Methods: Ten newly diagnosed FD patients and 10 age- and sex-matched asymptomatic controls were consecutively recruited at outpatient gastroenterology clinic of Sir Run Run Shaw Hospital. Endoscopic examination was performed in all participants and mucosa tissues were obtained from the duodenal bulb (D1) and the second portion of the duodenum (D2). Quantitative real-time polymerase chain reaction (qRT-PCR) and immunohistochemistry (IHC) were used to evaluate autophagy proteins (beclin1, p62/SQSTM1) at transcriptional and translational levels, respectively. Results: 1. Immunostaining of duodenal tissues revealed a significantly decreased beclin1 protein expression both in D1 (4.9±2.7 vs. 8.0±3.6, P =0.038) and D2 (5.7±2.3 vs. 9.2±2.4, P =0.003) of FD patients compared with asymptomatic controls. 2. When stained for p62, the number of positive cells was significantly higher in D1 (8.1±3.2 vs. 3.7±2.0, P =0.001), but similar in D2 (10.3±5.0 vs. 9.1±4.3, P = 0.661 ) of FD patients compared with asymptomatic controls. 3. There was no difference of beclin1 mRNA expression in D1 (0.01±0.01 vs. 0.02±0.02, P =0.50) and D2 (0.05±0.03 vs. 0.07±0.05, P =0.42) between FD patients and asymptomatic controls. 4. No difference of p62 mRNA expression in D1 (0.03±0.02 vs. 0.05±0.04, P =0.22) and D2 (0.02±0.01 vs. 0.03±0.03, P =0.33) was observed between FD patients and asymptomatic controls. Conclusions: The findings of this study provided that autophagy protein beclin1 was down-regulated in the duodenum and p62 was up-regulated in D1 of patients with FD, which indicated abnormal autophagy is potentially related to FD development.